Fargas y Rovira : Llull-Taulat, manzana 2, bloque PB+3 (2002)
Proyecto de renovación urbana en Barcelona con motivo del <Fórum>
Keywords: FARGAS-ROVIRA; BARCELONA; ESPAÑA; FARGAS, JORDI; ROVIRA, JOSEP M; PROYECTOS; VIVIENDAS MULTIFAMILIARES